2016
DOI: 10.5301/jbm.5000187
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR in Relation to Epithelial-Mesenchymal Transition and Cancer Stem Cells in Molecular Subtypes of Endometrial Cancer

Abstract: Our data do not confirm the role of HOTAIR in EMT-mediated CSC formation in EC. Neither does the diversity of EC molecular subtypes influence these processes. But HOTAIR expression could serve as an independent prognostic factor in EC. The clinical importance of the above discoveries requires further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Simultaneously, HOTAIR could facilitate transformation of gastric cancer tissues from polarized epithelial cells to mobile mesenchymal cells, and also trigger abnormal expressions of genes relevant to EMT and cancer metastasis, including ICAM‐1, MMP1, MMP3, MMP9, and Snail . Correspondingly, knockout of HOTAIR could induce hindered EMT process, which could be reversed by addition of exogenous Snail . Hence, it was well‐explained that HOTAIR might facilitate the progression of gastric cancer through mediation of the EMT process in this study (Figure ).…”
Section: Discussionmentioning
confidence: 53%
“…Simultaneously, HOTAIR could facilitate transformation of gastric cancer tissues from polarized epithelial cells to mobile mesenchymal cells, and also trigger abnormal expressions of genes relevant to EMT and cancer metastasis, including ICAM‐1, MMP1, MMP3, MMP9, and Snail . Correspondingly, knockout of HOTAIR could induce hindered EMT process, which could be reversed by addition of exogenous Snail . Hence, it was well‐explained that HOTAIR might facilitate the progression of gastric cancer through mediation of the EMT process in this study (Figure ).…”
Section: Discussionmentioning
confidence: 53%
“…For instance, long noncoding RNA HOX antisense intergenic RNA (HOTAIR), closely associated with metastasis, epithelial–mesenchymal transition (EMT), and poor prognosis, has emerged as a key metastatic molecule in many cancers [810]. The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), the first lncRNA identified as an independent prognostic marker for nonsmall-cell lung cancer [11], was found to play an important role in the metastasis of various types of cancers [1214].…”
Section: Introductionmentioning
confidence: 99%
“…[85][86][87][88][89] HOTAIR expression supports metastasis in breast cancer and has been linked to poor outcome in several malignancies. 85 Padua Alves et al 86 examined breast and colon cancer cell lines in studies of HOTAIR regulation and found that this lncRNA was increased after TGFβ1 treatment in both breast and colon cancers.…”
Section: Hox Transcript Antisense Intergenic Rna (Hotair)mentioning
confidence: 99%
“…86 HOTAIR has also been implicated in the regulation of CSCs in cervical cancer and endometrial cancer. [87][88][89] LINC-ROR Linc-ROR was first discovered in induced pluripotent stem cells (iPSCs) where it was regulated by the key pluripotency factors Oct4, Sox2 and Nanog. 90 Linc-ROR has a principal role in maintenance of iPSCs and embryonic stem cells by preventing the activation of cellular stress pathways including the p53 response.…”
Section: Hox Transcript Antisense Intergenic Rna (Hotair)mentioning
confidence: 99%